The effects of progressive muscle relaxation exercise applied to lung cancer patients receiving chemotherapy on dyspnea, pain and sleep quality: A randomized controlled trial - Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Sarikose, Aysegul (Elsevier Sci Ltd, 2024)
Purpose: The aim of the present study is the analysis of how progressive muscle relaxation exercise affects dyspnea, pain and sleep quality in patients with lung cancer receiving chemotherapy. Methods: Seventy-four patients diagnosed with lung cancer were included in this randomized controlled study. A total of 16 sessions of progressive muscle relaxation exercises were applied to the patients in the intervention group for a duration of 30 min, 2 days a week for 8 weeks. Patient Information Form, Medical Research Council Dyspnea Scale (MRC dyspnea scale), Pitssburg Sleep Quality Index (PSQI), Visual Analog Scale- Pain (VAS -P) were used to collect data. Results: Socio-demographic and disease characteristics were found to be similar in control and intervention groups. Final scores indicated significant differences between the experimental and control groups in all variables. The experimental group showed significantly more favorable results in dyspnea (p < 0.001), pain (p < 0.003) and sleep (p < 0.001) symptoms. When the effect size values (Cohen 's d) of these findings were analyzed, PMR exercise was found to have a moderate effect on mean VAS -P scores (0.548) and a large effect on mean MRC dyspnea scale (1.073) and PSQI (0.970) scores. These results indicated significant differences in pre and post intervention mean scores. Conclusion: Progressive muscle relaxation exercise applied to lung cancer patients receiving chemotherapy was found to be effective in reducing dyspnea and pain severity and improving sleep quality. Clinical trial registration at ClinicalTrials.gov. NCT04978805
Keywords: Pain; Lung cancer; Dyspnea; Sleep; Progressive muscle relation; Exercise